Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Substituting x = – 3 in x^2 – 5x + 4 gives (– 3)^2 – 5( – 3)+4 = 9–15+4 = – 2

Substituting x = – 3 in
x^2 – 5x + 4 gives (– 3)^2 – 5( – 3)+4 = 9–15+4 = – 2

Grade:12

1 Answers

Anand Kumar Pandey
askIITians Faculty 5653 Points
2 months ago
Dear Student

Substituting x =–3 in x^2–5x+4
x^2–5x+4 = (–3)^2–5(–3)+4 = 9+15+4 = 28.
This is the correct answer

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free